Analisis Kemampuan Siswa dalam Menyelesaikan Soal-Soal Fisika Pada Konsep Gerak Lurus dengan Menerapkan Model Pembelajaran Advance Organizer Pada Siwa di Kelas X SMA Negeri 8 Tidore Kepulauan - Nursanti Ali; Fahima Muhlis (Peneliti.net, 2021)
This study aims to determine the ability of students to solve problems on the concept of straight motion after the advance organizer learning model is applied. This research uses quantitative descriptive method with experimental research type pretest-posttest control group design. The subjects of this study were students of class X IPA at SMA Negeri 8 Tikep for the academic year 2019/2020, totaling 43 students spread over 2 classes, namely class X IPA 2 (as the experimental class) and X IPA 1 (as the control class). This research was conducted in August 2019 with the object of research being the ability of students to solve problems on the concept of straight motion. The data obtained from the results of the written test in the form of a description. The results of this study indicate that the average student learning outcomes increase. The average posttest learning outcomes using the advance organizer learning model in the experimental class was 81.02. Meanwhile, using the conventional learning model for the control class, the average value is 74.81. The results of the analysis of students' ability to solve problems in the experimental class obtained scores with very good criteria 47.6% and good 52.4%. While in the control class, scores with very good criteria were 18.12%, 72.7% good, and 9.1% enough.